Does Brand Ambassadors Drive Repurchase Intention? The Mediating Role of Brand Image and the Moderating Effect of Customer Engagement in the Skincare Industry - Nurul Hidayah; Elyza Fauziah; Yani Fuzi Ananti; Miftahul Jannah (Lentera Ilmu Nusantara, 2025)
In the midst of increasingly dynamic digital marketing competition, brand ambassadors are a widely used strategy to build brand image and increase consumer loyalty. This study aims to analyze the effect of brand ambassadors on repurchase intention of Somethinc skincare consumers in Bekasi City, with brand image as a mediating variable and customer engagement as a moderating variable. The research method used is quantitative with a descriptive-verification approach. Data were obtained through questionnaires from 100 respondents and analyzed using SEM-PLS through SmartPLS 3 software. The results showed that brand ambassadors have a significant influence on brand image, but have no direct effect on repurchase intention. Brand image act as mediator in this association, Meanwhile, customer engagement did not moderating relationship between brand ambassador on repurchase intention in this model. This finding indicates that positive perceptions of the brand and active consumer engagement are key in driving repurchase decisions. On the other hand, the interaction between brand ambassadors and customer engagement did not show a significant moderating effect. In conclusion, marketing strategies through brand ambassadors will be more effective if supported by a strong brand image and high customer engagement. The practical implication of this study is the need to select brand ambassadors that are aligned with brand identity and strengthen brand communication to build customer engagement.